DEVELOPMENT OF A WEB-BASED POINT OF SALE (POS) SYSTEM APPLICATION FOR MRS. SULASMI'S GROCERY STORE - Bian Dwi Pamungkas; Hendra Adi Saputra; Fahrur Rozi; Abdul Haris Indrakusuma (JoEICT (Jurnal of Education And ICT), 2023)
Mrs. Sulasmi grocery store is a grocery store that shells various types of goods. Mrs. Sulasmi grocery store has been established since 1998, and for almost 25 years or running the business, the store has not utilizied a supporting system for inventory recording and financial reporting. Due to the absence of such a system, store owners often face various fifficulties as monitoring inventory, calculating profit, lack of supervision over the security of good, and sometimes forgetting about product prices. ack of supervision over the security of goods, and sometimes forgetting about product prices. This research aims to develop a web-based point-of-sale (POS) system application that is suitable to assist Mrs. Sulasmi, the owner of the grocery store, in overcoming these challenges. The research methodology used is Research and Development (RnD) with a prototype development model consisting of 7 stages: (1) gathering requirements, (2) creating a prototype, (3) evaluating the prototype, (4) coding the system, (5) system testing, (6) system evaluation, and (7) system utilization. The assessment results from expert evaluators indicate that the developed product has achieved a very suitable criteria with a percentage of 100% for compatibility aspect and 100% for functional suitability aspect. Meanwhile, the field trial results indicate that the developed product has achieved a very satisfactory criteria with a score of 96.67. Based on the research findings, it can be concluded that the web-based point-of-sale system application for Mrs. Sulasmi grocery store is highly suitable for use.                                                                                                 Keywords: Web, Point of Sale, Grocery store